The PREMISE database of 20 Macaca fascicularis PET/MRI brain images available for research - Chalet, Lucie; Debatisse, Justine; Wateau, Oceane; Boutelier, Timothe; Wiart, Marlène; Costes, Nicolas; Mérida, Inés; Redouté, Jérôme; Langlois, Jean-Baptiste; Lancelot, Sophie; Léon, Christelle; Cho, Tae-Hee; et al. (Lab animal, 2024)
Non-human primate studies are unique in translational research, especially in neurosciences where neuroimaging approaches are the preferred methods used for cross-species comparative neurosciences. In this regard, neuroimaging database development and sharing are encouraged to increase the number of subjects available to the community, while limiting the number of animals used in research. Here we present a simultaneous positron emission tomography (PET)/magnetic resonance (MR) dataset of 20 Macaca fascicularis images structured according to the Brain Imaging Data Structure standards. This database contains multiple MR imaging sequences (anatomical, diffusion and perfusion imaging notably), as well as PET perfusion and inflammation imaging using respectively [ 15 O]H 2 O and [ 11 C]PK11195 radiotracers. We describe the pipeline method to assemble baseline data from various cohorts and qualitatively assess all the data using signal-to-noise and contrast-to-noise ratios as well as the median of intensity and the pseudo-noise-equivalent-count rate (dynamic and at maximum) for PET data. Our study provides a detailed example for quality control integration in preclinical and translational PET/MR studies with the aim of increasing reproducibility. The PREMISE database is stored and available through the PRIME-DE consortium repository. The authors present a simultaneous PET/MR dataset of 20 Macaca fascicularis images structured according to the Brain Imaging Data Structure standards. The PREMISE database is stored and available through the PRIME-DE consortium repository.